Navigating the Post-Industrial Recyclate Landscape Policy Implications, Market Dynamics, and Allocation Methodologies in Life Cycle Assessment - Gascon Rudin, Greta; Brantebäck, Daniel (My University, 2024)
This thesis explores the landscape of post-industrial recyclates (PIR), investigating policy, market trends, environmental impact, and life cycle assessment (LCA) allocation methods. The study takes the perspective of Borealis, a prominent player in the petrochemical industry, with a special focus on two of their recycling plants located in Germany and Austria. The policy analysis evaluates existing policies regarding PIR alongside a foresightbased scenario analysis. Findings reveal an absence of EU policy supporting PIR, contrasting with the abundance of policy support for post-consumer recyclates. The absence of policy support for PIR is likely due to its economic viability without such support, suggesting that current policy norms will persist. This sentiment is echoed by the scenario analysis, where no scenario indicated that PIR would require policy intervention to remain competitive in the market. The market analysis, which focused on the German market, identified younger demographics as key drivers of sustainable consumption, offering opportunities for PIR integration in sectors such as cosmetics, technology, and pet-related products. Additionally, consumers tend to consider the environmental impact of their purchases more when investing in expensive, long-lasting items, making furniture and household equipment promising markets. The analysis also explored the German automotive industry, where demand for recyclates is rising, although impending EU regulation may limit PIR’s potential. The LCA findings revealed a lower environmental impact for PIR compared to virgin polypropylene (PP) across 14 out of 16 impact categories. System expansion allocation yielded distinct outcomes as it accounts for the emissions avoided when substituting virgin PP with PIR. Conversely, other methods - mass allocation, economic allocation and the cut-off approach - yield similar results. While both mass and economic allocation were deemed appropriate, mass allocation emerges as the optimal choice, better reflecting real-world drivers behind plastic production and waste generation.
Keywords: post-industrial recyclate; plastic; recycling; life cycle assessment; allocation; policy; scenario analysis; market analysis; circular economy.